Satisfaction and Self-Confidence of Nursing Students in Learning using 3D Simulators - Adawiyah, Nabilah Al; Komariah, Maria; Kosim, Kosim (Universitas Padjadjaran, 2023)
Background: Face-to-face simulation requires a lot of resources, such as space, time, and cost. These obstacles encourage educators to look for learning technologies that can provide realistic learning opportunities and be accessed flexibly, one of which is by using virtual simulations such as 3D simulators. The effectiveness of 3D simulator as learning media can be assessed through student satisfaction and self-confidence.Aim: This study aims to identify nursing students' satisfaction and self-confidence in learning using 3D simulators.Method: The research design used was descriptive quantitative. The sampling technique used was purposive sampling with a sample of 67 nursing students. The instrument used was the Student Satisfaction and Self-Confidence in Learning Scale (SCSL). Data analysis was carried out using univariate analysis.Result: This study showed that students were very satisfied (M = 4.415; SD = 0.489) and very confident (M = 4.338; SD = 0.419) in learning using a 3D simulator.Conclusion: High satisfaction and self-confidence in using 3D simulators were obtained. The 3D simulator can be a supporting media that can be used in several nursing courses to prepare for practicum and as a medium for reviewing practicum that has been done. Keywords: 3D simulator, satisfaction, self-confidence, virtual simulation